The molecular function of kallikrein‐related peptidase 14 demonstrates a key modulatory role in advanced prostate cancer. Issue 1 (28th November 2019) - Kryza, Thomas; Bock, Nathalie; Lovell, Scott; Rockstroh, Anja; Lehman, Melanie L.; Lesner, Adam; Panchadsaram, Janaththani; Silva, Lakmali Munasinghage; Srinivasan, Srilakshmi; Snell, Cameron E.; Williams, Elizabeth D.; Fazli, Ladan; et al.
Abstract : Kallikrein‐related peptidase 14 (KLK14) is one of the several secreted KLK serine proteases involved in prostate cancer (PCa) pathogenesis. While relatively understudied, recent reports have identified KLK14 as overexpressed during PCa development. However, the modulation of KLK14 expression during PCa progression and the molecular and biological functions of this protease in the prostate tumor microenvironment remain unknown. To determine the modulation of KLK14 expression during PCa progression, we analyzed the expression levels of KLK14 in patient samples using publicly available databases and immunohistochemistry. In order to delineate the molecular mechanisms involving KLK14 in PCa progression, we integrated proteomic, transcriptomic, and in vitro assays with the goal to identify substrates, related‐signaling pathways, and functional roles of this protease. We showed that KLK14 expression is elevated in advanced PCa, and particularly in metastasis. Additionally, KLK14 levels were found to be decreased in PCa tissues from patients responsive to neoadjuvant therapy compared to untreated patients. Furthermore, we also identified that KLK14 expression reoccurred in patients who developed castrate‐resistant PCa. The combination of proteomic and transcriptomic analysis as well as functional assays revealed several new KLK14 substrates (agrin, desmoglein 2, vitronectin, laminins) and KLK14‐regulated genes (Interleukin 32, midkine, SRY‐Box 9), particularly an involvement of the mitogen‐activated protein kinase 1 and interleukin 1 receptor pathways, and an involvement of KLK14 in the regulation of cellular migration, supporting its involvement in aggressive features of PCa progression. In conclusion, our work showed that KLK14 expression is associated with the development of aggressive PCa suggesting that targeting this protease could offer a novel route to limit the progression of prostate tumors. Additional work is necessary to determine the benefits and implications of targeting/cotargeting KLK14 in PCa as well as to determine the potential use of KLK14 expression as a predictor of PCa aggressiveness or response to treatment. Abstract : Kallikrein‐related peptidase 14 (KLK14) is a secreted serine protease belonging to the kallikrein‐related‐peptidase family. We identified that KLK14 is overexpressed in advanced prostate cancer and acts on various substrates involved in adhesion, migration, and invasion of cancer cells, thus modulating genes and signaling pathways essential for prostate cancer progression. These results suggest that KLK14 is a potential target to control aggressiveness of prostate tumors.